The Transformation of English Language Pedagogy in the Context of Distance Education: A Literature Review on Challenges and Opportunities in the Digital Era (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This study aims to examine the transformation of English pedagogy in the context of distance education in the digital era. With the advancement of technology, distance education has become a primary alternative for delivering instructional content, including in English language teaching. This research employs a qualitative approach using the library research method to identify the challenges and opportunities in teaching English through distance education. The findings indicate that although there are challenges related to teacher readiness and limited access to technology for students, the digital era also offers significant opportunities to enrich learning through various interactive media and cross-cultural collaboration. Technology-based learning models, such as blended learning and flipped classroom, enhance student engagement and make learning more flexible. The study underscores the importance of developing digital competencies for teachers and ensuring adequate technological infrastructure for effective pedagogical transformation.